Super-resolution RESOLFT microscopy of lipid bilayers using a fluorophore-switch dyad - Frawley, AT; Wycisk, V; Xiong, Y; Galiani, S; Sezgin, E; Urbancic, I; Jentzsch, AV; Leslie, KG; Eggeling, C; Anderson, HL (Royal Society of Chemistry, 2020)
Dyads consisting of a photochromic switch covalently linked to a fluorescent dye allow the emission from the dye to be controlled by reversible photoisomerization of the switch; one form of the switch quenches fluorescence by accepting energy from the dye. Here we investigate the use of dyads of this type for super-resolution imaging of lipid bilayers. Giant unilamellar vesicles stained with the dyads were imaged with about a two-fold resolution-enhancement compared with conventional confocal microscopy. This was achieved by exciting the fluorophore at 594 nm, using a switch activated by violet and red light (405/640 nm).